Women's voices, feminist visions classic and contemporary readings - Shaw, Susan M. 1960- 1906-1998. 1933-; Lee, Janet 1954- 1952- (McGraw-Hill, 2012)
Women's stuides: perspectives and practices; Systems of privilege and inequality; Learning gender; Sex, power, and intimacy; Inscribing gender on the body; Health and reproductive rights; Family systems, family lives...